2011
DOI: 10.1530/erc-10-0343
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of chemotherapy resistance in castration-resistant prostate cancer

Abstract: Chemotherapy remains the major treatment option for castration-resistant prostate cancer (CRPC) and limited cytotoxic options are available. Inherent chemotherapy resistance occurs in half of all patients and inevitably develops even in those who initially respond. Docetaxel has been the mainstay of therapy for 6 years, providing a small survival benefit at the cost of significant toxicity. Cabazitaxel is a promising second-line agent; however, it is no less toxic, whereas mitoxantrone provides only symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 147 publications
2
74
0
Order By: Relevance
“…NF-κB inhibitors are known to decrease AR signalling in vitro and reduce the growth of androgen deprivation-resistant prostate cancer xenografts in vivo (Jin et al 2008, Zhang et al 2009b. However, at present no specific NF-κB inhibitors have reached the stage of clinical trials for prostate cancer treatment (Mahon et al 2011). Our results support NF-κB as the main mediator of monensin induced oxidative stress, which may also contribute to the reduced androgen signalling and induction of apoptosis in monensin exposed prostate cancer cells.…”
Section: Resultssupporting
confidence: 65%
“…NF-κB inhibitors are known to decrease AR signalling in vitro and reduce the growth of androgen deprivation-resistant prostate cancer xenografts in vivo (Jin et al 2008, Zhang et al 2009b. However, at present no specific NF-κB inhibitors have reached the stage of clinical trials for prostate cancer treatment (Mahon et al 2011). Our results support NF-κB as the main mediator of monensin induced oxidative stress, which may also contribute to the reduced androgen signalling and induction of apoptosis in monensin exposed prostate cancer cells.…”
Section: Resultssupporting
confidence: 65%
“…Furthermore, many signaling pathways have been associated with chemotherapy resistance, including the Wnt signaling pathway (36)(37)(38)(39)(40). Previous studies indicated that dysregulation of the Wnt/β-catenin signaling pathway is involved in pancreatic cancer chemoresistance (39).…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel functions as an inhibitor of microtubular depolymerization (30). In addition to microtubular dynamics, multiple cellular pathways involving apoptosis, inflammation, angiogenesis, signaling intermediaries, and drug efflux pumps have been implicated in the chemosensitivity of docetaxel (31). Previous and present data indicate that the FGFR2IIIb signaling pathway induces apoptosis and furthermore might suppress EMT or at least reverse it, which has been reported to prevent the apoptosis of cancer cells and to induce resistance to chemotherapy (29,32).…”
Section: Discussionmentioning
confidence: 66%
“…4. Survivin and XIAP are a family of inhibitors of apoptosis proteins (IAPs) that promote cell survival by inhibiting the caspase cascade and apoptosis (31,33). Survivin and XIAP are the most studied IAPs with regard to resistance to anticancer agents.…”
Section: Discussionmentioning
confidence: 99%